Borgerkrig fra Athen til Auschwitz:: Et essay om de politiske (u-)muligheder i Agambens tænkning - Flohr, Mikkel (Slagmark - Tidsskrift for idéhistorie, 2015)
The starting point of this article is the concept of civil war in Giorgio Agamben’s Homo Sacer-series. In spite of its relative obscurity, Agamben insists that civil war is the fundamental political structure, which has characterized all of Western history since Ancient Greece. As such it constitutes a privileged vantage point from whence it is possible to discern the limitations of his political thought. These limitations originate in his deployment of Carl Schmitt’s state of exception, which serves to include civil war in the sovereign order – this entails that classical modes of political contestation and conflict e.g. revolution, are always already internal to the sovereign state, and can therefore only serve to reaffirm it. The state of exception thus produces an inherent incapacity to think or move beyond the sovereign state. Agamben subsequently attempts to challenge the state of exception albeit with varying degrees of success. This suggest the necessity of taking exception to the exception and explode the conceptual coupling of civil war and sovereign power, in order to create a space where it is possible to think political contestation within or beyond the works of Agamben.